European court of human rights as a guarantee of observation the medical secrecy - Olena V Prudnykova; Vasil M Pyvovarov; Olena V Fedosova; Oksana A Stasevska; Olga V Umanets (Wolters Kluwer Medknow Publications, 2021)
The European Convention on Human Rights proclaims the right of everyone to privacy of information about their state of health, which is a particularly important issue during the COVID-19 pandemic. The aim of the study is to determine the essence of the ECtHR's activity as a guarantee of information culture, highlight the main elements of its activities in this aspect, and analyze the right to medical secrecy in the practice of the European Court of Human Rights. The formal-logical method was used to analyze the norms of the European Convention on Human Rights, determine the content of basic concepts, and systematize the material in order to obtain generalizing conclusions within the framework of the stated problem. The predictive method was used to determine the prospects for the development of legislation aimed at creating a system of effective legal provision for the confidentiality of patient information. The European Court of Human Rights has more than once drew attention to the enormous importance of protecting personal, in particular medical data, so that a person can enjoy his or her right to private and family life with satisfaction. That is why public authorities must ensure the confidentiality of information about the health of individuals. It should not be disclosed or processed without the prior informed consent of the person concerned. There are a lot of cases of unlawful disclosure of information about the patient's health and liability for unlawful disclosure.